Network Analysis of UBE3A/E6AP-Associated Proteins Provides Connections to Several Distinct Cellular Processes. Issue 7 (30th March 2018) - Martínez-Noël, Gustavo; Luck, Katja; Kühnle, Simone; Desbuleux, Alice; Szajner, Patricia; Galligan, Jeffrey T.; Rodriguez, Diana; Zheng, Leon; Boyland, Kathleen; Leclere, Flavian; Zhong, Quan; Hill, David E.; et al.
Abstract: Perturbations in activity and dosage of the UBE3A ubiquitin-ligase have been linked to Angelman syndrome and autism spectrum disorders. UBE3A was initially identified as the cellular protein hijacked by the human papillomavirus E6 protein to mediate the ubiquitylation of p53, a function critical to the oncogenic potential of these viruses. Although a number of substrates have been identified, the normal cellular functions and pathways affected by UBE3A are largely unknown. Previously, we showed that UBE3A associates with HERC2, NEURL4, and MAPK6/ERK3 in a high-molecular-weight complex of unknown function that we refer to as the HUN complex ( H ERC2, U BE3A, and N EURL4). In this study, the combination of two complementary proteomic approaches with a rigorous network analysis revealed cellular functions and pathways in which UBE3A and the HUN complex are involved. In addition to finding new UBE3A-associated proteins, such as MCM6, SUGT1, EIF3C, and ASPP2, network analysis revealed that UBE3A-associated proteins are connected to several fundamental cellular processes including translation, DNA replication, intracellular trafficking, and centrosome regulation. Our analysis suggests that UBE3A could be involved in the control and/or integration of these cellular processes, in some cases as a component of the HUN complex, and also provides evidence for crosstalk between the HUN complex and CAMKII interaction networks. This study contributes to a deeper understanding of the cellular functions of UBE3A and its potential role in pathways that may be affected in Angelman syndrome, UBE3A-associated autism spectrum disorders, and human papillomavirus-associated cancers. Graphical abstract: Highlights: UBE3A is associated with Angelman syndrome, autism, and HPV-associated cancers. Several new UBE3A-associated proteins were identified (e.g., MCM6 and ASPP2). UBE3A-associated proteins are connected to several fundamental cellular processes. There is evidence for crosstalk between UBE3A and CAMKII interaction networks. Network analyses provide new insights into the cellular functions of UBE3A.